Pengaruh Struktur Kepemilikan Terhadap Kebijakan Dividen Perusahaan Manufaktur Yang Terdaftar Di BEI - Henny S. Lestari, Haura R. T. Effendi, Ferina A. Latiefa, (Jurnal Ekonomi, 2021)
The purpose of this research is to conclude the impact of ownership structure on dividend yield. The sample in this study are companies from the manufacturing sector listed on Indonesia Stock Exchange in 2016-2020. The sampling technique used in this study is purposive sampling and the analysis method is panel data regression. The independent variables in this study are institutional ownership, foreign ownership and government ownership, and the control variable is profitability, with the dividend yield as the dependent variable. The results show that foreign ownership and profitability have a positive effect on dividend yield, while institutional ownership and government ownership have no effect on dividend yield. This study is expected to give implication for company managers. by paying attention to the amount of profit earned so that shareholders get dividend yield, and also expected to be a source of information for potential investors to see the level of profit and dividend yield given by the company to shareholders.